2001
DOI: 10.1038/sj.onc.1204296
|View full text |Cite
|
Sign up to set email alerts
|

UCS15A, a non-kinase inhibitor of Src signal transduction

Abstract: Src tyrosine kinase plays key roles in signal transduction following growth factor stimulation and integrinmediated cell-substrate adhesion. Since src-signal transduction defects are implicated in a multitude of human diseases, we have sought to develop new ways to identify small molecule inhibitors using a yeast-based, activatedsrc over-expression system. In the present study, we describe the identi®cation of a unique src-signal transduction inhibitor, UCS15A. UCS15A was found to inhibit the src speci®c tyros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 67 publications
3
45
0
1
Order By: Relevance
“…This proposal is consistent with previous reports showing that the binding of Tsk5 to Src SH3 plays an essential role in podosome formation (Oikawa et al, 2008;Seals et al, 2005). The crucial role of the SH3 domain in Src function was also exemplified by other previous studies using UCS15A, which is a drug that blocks SH3-mediated protein-protein interaction (Hashimoto et al, 2006;Oneyama et al, 2002;Sharma et al, 2001). On the basis of these previous studies, we decided to examine further the 1734 Journal of Cell Science 124 (10) function of the Src SH3 domain by identifying additional Src SH3 binding partners.…”
Section: Discussionsupporting
confidence: 81%
“…This proposal is consistent with previous reports showing that the binding of Tsk5 to Src SH3 plays an essential role in podosome formation (Oikawa et al, 2008;Seals et al, 2005). The crucial role of the SH3 domain in Src function was also exemplified by other previous studies using UCS15A, which is a drug that blocks SH3-mediated protein-protein interaction (Hashimoto et al, 2006;Oneyama et al, 2002;Sharma et al, 2001). On the basis of these previous studies, we decided to examine further the 1734 Journal of Cell Science 124 (10) function of the Src SH3 domain by identifying additional Src SH3 binding partners.…”
Section: Discussionsupporting
confidence: 81%
“…Other studies have shown that a similar e ect can be seen with as little as 0.5 mM of UCS15A (data not shown). As demonstrated previously (Sharma et al, 2001), the intracellular level of Sam68 was unaltered by drug treatment (Figure 1b, top left panel). Since there is some ambiguity as to whether Sam68 interacts with Src via its SH2 or its SH3 domain, the mode of interaction of Sam68 with Src, in the HCT116 cell system, was investigated further.…”
Section: Inhibition Of the Association Of C-src With Sam68 By Ucs15a supporting
confidence: 60%
“…While Src binding to Sam68 involves both the SH2 and SH3 domains of Src, it has been proposed that Sam68 interacts initially with the SH3 domain of Src and is subsequently tyrosine phosphorylated by Src, speci®-cally during mitosis, and results in the high a nity binding of Sam68 to Src via its SH2 domain (Shen et al, 1999). Previous studies had shown that in v-Src transformed mouse ®broblasts, UCS15A inhibited the tyrosine phosphorylation of Src substrates, such as Sam68 and cortactin and also induced the disruption of the Src ± Sam68 complex (Sharma et al, 2001). To further investigate the mechanism of action of UCS15A, the e ect of the drug on Src-mediated protein ± protein complexes were examined in HCT116 cells (Figure 1).…”
Section: Inhibition Of the Association Of C-src With Sam68 By Ucs15a mentioning
confidence: 99%
See 1 more Smart Citation
“…25,102 AP22408 and AP23451 are bone-targeted Src inhibitors that inhibit tyrosine kinase activity. AP22408 has demonstrated antiosteoclast and antiresorptive Dasatinib (BMS-354825) [79][80][81][82][83][84][85][86] Src, Lyn, Bcr-Abl, c-kit, PDGFR, ephrin AZD-0530 [87][88][89][90][91][92][93][94][95][96] Src, Bcr-Abl Bosutinib (SKI-606) [97][98][99] Src, Bcr-Abl XL999 100,101 Src, VEGFR2, c-kit, PDGFR, FGFR1 CGP77675 25,102 Src, Lck, Yes, EGFR, VEGFR, FAK CGP76030 103 Src, Lck, Yes, Bcr-Abl AP22408 104 Src AP23451 105 Src UCS15A 106 Src AP22161 107 Src S1 peptide 108 Src/androgen receptor interaction activity in vitro and in vivo. 104 AP23451 prevented osteolytic lesions in mice inoculated with a human breast cancer cell line.…”
Section: Angiogenesismentioning
confidence: 99%